Chemical shift encoding (CSE) for sensitive fluorine‐19 MRI of perfluorocarbons with complex spectra. Issue 5 (1st September 2017) - van Heeswijk, Ruud B.; Colotti, Roberto; Darçot, Emeline; Delacoste, Jean; Pellegrin, Maxime; Piccini, Davide; Hernando, Diego
Abstract : Purpose: To implement a fluorine‐19 ( 19 F) chemical shift encoding (CSE) approach for the sensitive imaging of molecules with multi‐resonance spectra to remove their chemical shift displacement (CSD) artifacts, and to characterize its sensitivity versus established pulse sequences. Methods: The feasibility of CSE spoiled gradient echo (GRE) and balanced steady‐state free precession (bSSFP) was first demonstrated in a phantom study. The dependence of the sensitivity of CSE‐bSSFP on several pulse sequence parameters was then established, after which the occurrence of out‐of‐plane excitation was assessed for 2D and 3D techniques. Next, the sensitivity (in mm −3 s −0.5 ) of both CSE techniques was compared to bSSFP ultrashort echo time (bSSFP‐UTE) imaging and multi‐chemical‐shift‐selective turbo spin echo (MCSS‐TSE) in a second phantom study. Finally, the sensitivity of the CSE‐bSSFP, bSSFP‐UTE, and MCSS‐TSE pulse sequences was compared in a preliminary in vivo mouse study. Results: Both CSE approaches were successfully implemented and resulted in negligible residual CSD artifacts, while large‐volume 3D acquisitions should be considered to reduce problems related to out‐of‐plane excitation. CSE–bSSFP was shown to have a higher sensitivity than the bSSFP‐UTE and MCSS‐TSE pulse sequences (15.8 ± 1.3 vs. 11.7 ± 1.0 vs. 13.3 ± 0.9 mm −3 s −0.5, respectively, P < 0.001), whereas CSE‐GRE technique had a lower sensitivity (4.8 ± 1.1 mm −3 s −0.5 ). Conclusion: CSE 19 F MR imaging enables the unambiguous visualization of compounds with complex spectra, and provides high sensitivity both in vitro and in vivo. Magn Reson Med 79:2724–2730, 2018. © 2017 International Society for Magnetic Resonance in Medicine.